Aqueous ethanol laminar burning velocity measurements using constant volume bomb methods. (15th February 2018) - Hinton, N.; Stone, R.; Cracknell, Roger; Olm, Carsten
Abstract: Ethanol is attractive as a renewable fuel for spark ignition engines, and can also be used as an extender in gasoline (up to about 20% by volume) or as a major component (say above 70% by volume). There are three reasons for wanting to know the laminar burning velocity of water/ethanol/air mixtures. The first reason is that a significant fraction of the fuel calorific value is required to remove the last 10 per cent or so by volume of water from bio-ethanol, and in some applications it might not be necessary to remove all the water. The second reason is to provide extended data for model validation. The third reason is that in turbocharged engines the knock-free operating range can be extended through water addition so as to improve both output and efficiency. Laminar burning velocity measurements with up to 40% water by volume have been made with a constant volume combustion vessel using two distinct techniques: a) imaging of the flame front during the constant pressure period and b) analyzing the pressure rise data. When the pressure rises the adiabatic core is compressed isentropically, so if a combustion model is used, a single experiment generates a sequence of measurements that include data at high temperatures (up to 600 K) and high pressures (up to 12 bar) that are relevant to spark ignition engine combustion. Data from the two methods is shown here to be consistent and in-line with published data for ethanol, and satisfactory comparisons have also been found with predictions from kinetic mechanisms for the ethanol/water/air mixtures. The constant volume combustion vessel also generates data on the Markstein length and the pressure at the onset of cellularity, with both being increased by the presence of water. The laminar burning velocity has a direct influence on the early flame growth in a spark ignition engine, and unless the ignition timing is adjusted for slow burning mixtures there will be a significant loss of efficiency. Engine data show that even with 40% water by volume in the ethanol, combustion performance is still acceptable if the ignition timing is advanced.